Efficient Multiple Sequences Alignment Algorithm Generation via Components Assembly Under PAR Framework - Shi, Haipeng; Shi, Haihe; Xu, Shenghua (Frontiers in Genetics, 2021)
As a key algorithm in bioinformatics, Sequence alignment algorithm is widely used in sequence similarity analysis and genome sequence database search. Existing research mainly focuses on the specific steps of the algorithm or is for specific problems, lack of high-level abstract domain algorithm framework. Multiple sequence alignment algorithms are more complex, redundant and difficult to understand, and it is not easy for users to select the appropriate algorithm, as a result some computing errors may be caused. Based on our constructed pairwise sequence alignment algorithm component library and the convenient software platform PAR, a few expansion domain components are developed for multiple sequence alignment application domain, and specific multiple sequence alignment algorithm can be designed and its corresponding program, i.e., C++/Java/Python program, can be generated efficiently, thus enables the improvement of the development efficiency of complex algorithms as well as accuracy of sequence alignment calculation. A star alignment algorithm is designed and generated to demonstrate the development process.